Prezentowanie własnych zainteresowań, uzdolnień i poglądów uczniów na forum publicznym - Obrębska, Barbara (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2002)
The article shows how it is possible to present students’ abilities, skills and views in public. It was mostly focused on class and school presentations. The following forms of activities which enable promoting students in public were taken into account: participating in competitions, circles оf interests (for example Polish language, theatre, film or culture) and school organisations (school committee); editting school newspapers; taking part in scientific sessions; organizing trips. The statment includes both the theoretical part and the examples of activities (checked in the pedagogical practise). It was emphasized that presenting skills, interests and views by students adjusted to the age and needs of young people prepared them to achieve the full maturity both in individual and social aspect.